Sensitivity Analysis for the Shimmy Dynamics of an Airplane Main Landing Gear - Romero, F. A. (Journal of Applied Nonlinear Dynamics, 2026)
Landing gear shimmy is the name given to the wobbling motion due to torsional vibration and lateral flexing of a landing gear leg. Depending on the airplane requirements Main Landing Gears have different configurations. In this paper we analyze the sensitivity responses of the shimmy dynamics of a main landing gear for different geometric configurations. The dynamics are expressed in terms of three different degrees of freedom. We focus on the geometry of the main landing gear, specifically how the side-stay attachment point inclination angle affects shimmy.